LAWYERS AND INTERCESSORS TO FIND A GOOD DEATH IN THE COSTA RICA OF XVII CENTURY - Velázquez Bonilla, Carmela (2013)
The work presented about finding lawyers and advocates to help before death and the particular judgment of the members of society during the colonial Costa Rica must be analyzed from the collective mentalities. From these conceptions of colonial society were based on the establishments of the Catholic Church. Therefore, expectations and rituals for help before death responded to what was seen as a mandate of the “Holy Mother Church” to prepare for “good death” in order to obtain as all practicing Christians a space in the “eternal glory”.